When the Levees Broke a Requiem in Four Acts - Lee, Spike; Charles, Cliff (Warner, 2007)
Principally structured as an oral history, Spike Lee's four-hour HBO documentary charts the horrific events that have devastated New Orleans in the last 12 months. The many stories of the bureaucratic bungling, political scapegoating and personal traumas in the aftermath of Hurricane Katrina are as shocking as the footage of death and suffering during the storm itself. Lee's invaluable film is shot through with feelings of pain, outrage and exasperation, returning again and again to the question of how the world's richest country could let this happen to its own people. Two un-shocking answers: race and money. [www.eyeweekly.com]
Keywords: DVD-Video